Creating conditions for Canadian aboriginal health equity: the promise of healthy public policy. Issue 1 (December 2016) - Richmond, Chantelle; Cook, Catherine
Abstract In the Canadian context, the persistence and growth of Aboriginal health and social inequity signals that we are at a critical public health policy juncture; current policy reflects an historic relationship between Aboriginal people and Canada that fails the contemporary health needs of Canada's Aboriginal peoples. In this review, we highlight the need for healthy public policy that recognizes and prioritizes the rights of Canada's Aboriginal people to achieve health equity. Drawing from a structural approach, we examine the historical scope and comprehensive breadth of the Indian Act in shaping modern Aboriginal health and social inequities. Canada's failure to implement a national public policy for Aboriginal health reflects the proliferation of racism in modern day Canada, and a distinctly lacking political will at the federal level. Despite these structural challenges, there is great promise in community self-determination in health care and the role of community-led research as advocacy for policy reform. In our conclusion, we turn to the Report on the Truth and Reconciliation Commission of Canada (2015) and draw upon the concept of reconciliation as a fundamental precursor for Aboriginal health equity. The burden of systemic change needed to promote healthy public policy cannot be carried by any single group of advocates; it is a shared responsibility that will require the collaboration and integration of various actors and knowledges.